'Made in China'. Contraband, Labour and the Gendered Effects of 'Free-Trade', China-Peru. Issue 3 (4th March 2017) - Ødegaard, Cecilie Vindal
Abstract : In Peru, textiles have increasingly become contested as commodities and objects of consumption, especially following the free trade agreement between Peru and China, signed in 2009, which accommodates increased importation of Chinese textiles. This article discusses how local intermediaries, often women who have found a livelihood working with the importation and vending of textiles, are affected by increased border regulations and competition from over-seas, more formalised forms of importation. Reflecting on enactments of femininities and the social and spatial embeddedness of trade in the border areas, the article discusses the multifaceted and gendered implications of a de-localisation of commodity flows.